2019
DOI: 10.1039/c8nr10383f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and migration of alkali metals (Li, Na, and K) on pristine and defective graphene surfaces

Abstract: Identification of defects proved to be beneficial for metal storage and adsorption on graphene, but are detrimental to metal migration, hence affecting the battery performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
155
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 83 publications
(130 reference statements)
12
155
0
1
Order By: Relevance
“…This is because during the process of destroying the graphite close‐packed structure, a large number of defects and oxygen‐containing groups are formed on the surface of the graphene, which increases the degree of surface disorder of the 3D ECG. Interestingly, these defects have a significant positive impact on increasing the lithium storage capacity of carbon materials …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because during the process of destroying the graphite close‐packed structure, a large number of defects and oxygen‐containing groups are formed on the surface of the graphene, which increases the degree of surface disorder of the 3D ECG. Interestingly, these defects have a significant positive impact on increasing the lithium storage capacity of carbon materials …”
Section: Resultsmentioning
confidence: 99%
“…The cathodic peak at around 1.4 V might originate from the reaction of Li ions with functional groups on the surfaces of 3D ECG . The cathodic peak (0.5 V) in the 1st cycle and disappeared in the following cycles could be assigned to the decomposition of the electrolyte and formation of solid electrolyte interphase (SEI) film . A pair of redox peaks below 0.2 V corresponds to the insertion and extraction of Li ions in the graphite layer .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] In addition, previous computational studies have suggested that the edge and defect sites on the carbon surface allow sodium to be adsorbed in the high-potential region. [12][13][14][15][16] The present generally accepted view is that hard carbon involves three types of storage sites: 1) the defects and edges on the graphene, 2) graphene-graphene interlayers, and 3) nanopores. However, the assignment of the aforementioned three storage mechanisms to the charge-discharge voltage profile is still controversial.…”
Section: Doi: 101002/aenm201903176mentioning
confidence: 99%